Toward High-Quality Education in Peru : Standards, Accountability, and Capacity Building - World Bank (Washington, DC, 2012)
One of the principal challenges in reducing poverty and accelerating development in Peru is improving the quality of education. This book is a contribution from the World Bank to the debate over how to improve the quality of education. The book has three main recommendations that, to be successful, should be implemented sequentially. First, it is necessary to generate basic standards, quality goals, and quality measurement systems. Second, once quality can be measured a clear system of accountability should be implemented based on these standards and quality goals. Third, once there are standards and systems of accountability, investment is needed to strengthen the institutional capacity of the providers.